2016
DOI: 10.1021/acs.est.5b06095
|View full text |Cite
|
Sign up to set email alerts
|

Mono- to Octachlorinated Polychlorinated Dibenzo-p-dioxin and Dibenzofuran Emissions from Sintering Plants Synergistically Controlled by the Desulfurization Process

Abstract: ABSTRACT:The influence of desulfurization systems in sintering plants on polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/F) concentrations, profiles, and emission factors was studied. Mono-to tri-CDD/Fs and tetra-to octa-CDD/F concentrations were 4.4 ± 2.3 and 10.5 ± 8.3 ng m −3, respectively, at the inlets and 0.87 ± 0.48 and 0.47 ± 0.22 ng m −3 , respectively, after desulfurization. The toxic equivalents (TEQs) were 0.95 ± 0.093 and 0.51 ± 0.040 ng of I-TEQ m −3 at the inlets and after desulfurizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
(68 reference statements)
3
21
1
Order By: Relevance
“…The PCDD/F, dl-PCB, PCN, and PBDE concentrations in the fly ash samples from heads and tails of the SNT machines sampled in this study, as well as values from the literature are shown in Table S2. The PCDD/F TEQ concentrations in the fly ash sampled at the heads and tails of the sintering machines were 2.00-63.1 and 0.25-1.41 ng g −1 , which were slightly higher than values of 0.17-0.88 ng g −1 reported by Wang et al [32]. The dl-PCB concen-trations in the fly ash sampled from the heads and tails of the sintering machines were 1.20-5.49 and 0.10-5.12 ng g −1 , which were comparable to values of 0.49−1.47 ng g −1 reported by Wang et al [33].…”
Section: Chlorinated and Brominated Persistent Organic Pollutant Conccontrasting
confidence: 67%
“…The PCDD/F, dl-PCB, PCN, and PBDE concentrations in the fly ash samples from heads and tails of the SNT machines sampled in this study, as well as values from the literature are shown in Table S2. The PCDD/F TEQ concentrations in the fly ash sampled at the heads and tails of the sintering machines were 2.00-63.1 and 0.25-1.41 ng g −1 , which were slightly higher than values of 0.17-0.88 ng g −1 reported by Wang et al [32]. The dl-PCB concen-trations in the fly ash sampled from the heads and tails of the sintering machines were 1.20-5.49 and 0.10-5.12 ng g −1 , which were comparable to values of 0.49−1.47 ng g −1 reported by Wang et al [33].…”
Section: Chlorinated and Brominated Persistent Organic Pollutant Conccontrasting
confidence: 67%
“…Figure 5 shows the insertion force vs. displacement curves for different lay-up sequences. It can be seen that a typical two-phase penetration mechanic 19,20 is shown for both unidirectional prepreg and cross-ply prepreg. In the compression phase (Phase I), the prepreg is in the elastic loading stage when the Z-pin tip is pressed against the prepreg surface.…”
Section: Fracture Mechanism Analysismentioning
confidence: 90%
“…Desulfurization operations have been found to remove various other pollutants, including dust and NOx, alongside SO 2 . We previously reported that desulfurization operations also remove PCDD/Fs from IOSPs’ stack gases . However, insofar as we are aware, no systematic study of the removal of PBDD/Fs from IOSPs’ stack gases by desulfurization operations has yet been described.…”
Section: Introductionmentioning
confidence: 96%
“…Approximately 40% of global iron ore sintering (more than in any other country) occurs in China where the industry includes many small, energy-inefficient IOSPs that emit relatively large amounts of pollutants. Eliminating old, small, inefficient IOSPs and encouraging the use of more advanced technologies indirectly decreases CO 2 , SO 2 , NO X , and PCDD/F emissions. However, the effects of these measures on decreasing PBDD/F emissions in China have not been estimated.…”
Section: Introductionmentioning
confidence: 99%